Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

hello ambassador

start with
\[2x^2-8x+7=0\] then use
\[x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}\] with \(a=2,b=-8,c=7\)

second step is
\[x=\frac{8\pm\sqrt{8^2-4\times 2\times 7}}{2\times 2}\] then a bunch of arithmetic

rewrite \(\sqrt{8}\) as \(2\sqrt{2}\) then factor and cancel
details are above

it is because \(\sqrt{8}=\sqrt{4\times 2}=\sqrt{4}\sqrt{2}=2\sqrt{2}\) in simplest radical form

then be careful with factoring before you cancel the common factor of 2 top and bottom

it could be written as
\[2\pm\frac{\sqrt{2}}{2}\]

Satellite is right, I was about to say that :)